Training on Making Solid Soap from Used Cooking Oil in Amol Village, East Miomafo District - Risna Erni Yati Adu; Gebhardus Djugian Gelyaman; Jefry Presson (Dewan Pimpinan Daerah (DPD) Perkumpulan Dosen Indonesia Semesta (DIS) Jawa Timur, 2023)
Waste cooking oil is heated at a high temperature of 160-250°C for a long time, causing oxidation, hydrolysis, and polymerization to produce ketones, aldehydes, and polymers that are detrimental to human health. Therefore, it is not recommended for reuse. Waste cooking oil in Amol Village was abundant and accommodated, often used repeatedly and then dumped into the environment without any further treatment. The initial survey showed that most of Amol Village's people do not yet know about the dangers of reusing used cooking oil or the dangers to the environment. On the other hand, high free fatty acids have the potential to be converted into soap through the saponification process with a base. Thus, the socialization of the dangers of waste cooking oil for human health and the environment and training on making solid soap from used cooking oil was carried out in Amol Village to assist the community in dealing with used cooking oil waste and save spending on soap purchases. Problem-solving was carried out through several stages of activities, namely observation, preparatory activities, socialization; manufacture of solid soap product from used cooking oil. Those stages were carried out through demonstrations and practices independently by participants, followed by monitoring, evaluation, and reporting. The knowledge and skills of participants have been improved, regarding to handling the used cooking oil and its processing into solid soap.